Functional interactions between the macaque dorsal and ventral visual pathways during three-dimensional object vision. (January 2018) - Janssen, Peter; Verhoef, Bram-Ernst; Premereur, Elsie
Abstract: The division of labor between the dorsal and the ventral visual stream in the primate brain has inspired numerous studies on the visual system in humans and in nonhuman primates. However, how and under which circumstances the two visual streams interact is still poorly understood. Here we review evidence from anatomy, modelling, electrophysiology, electrical microstimulation (EM), reversible inactivation and functional imaging in the macaque monkey aimed at clarifying at which levels in the hierarchy of visual areas the two streams interact, and what type of information might be exchanged between the two streams during three-dimensional (3D) object viewing. Neurons in both streams encode 3D structure from binocular disparity, synchronized activity between parietal and inferotemporal areas is present during 3D structure categorization, and clusters of 3D structure-selective neurons in parietal cortex are anatomically connected to ventral stream areas. In addition, caudal intraparietal cortex exerts a causal influence on 3D-structure related activations in more anterior parietal cortex and in inferotemporal cortex. Thus, both anatomical and functional evidence indicates that the dorsal and the ventral visual stream interact during 3D object viewing.